THE EFFECT OF BURGREENS PRODUCT COMMUNICATION TOWARD CONSUMER TRUST IN SOUTH JAKARTA - Alida Vanesha Putri; Sarah Najoan (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
Business communication develops relational strategies to build the consumers’ trust. The lack of Vegetables and fruit consumption motivates Burgreens’ owner to create healthy fast food.Therefore,trust engages society to be involved in order to begin a healthy lifestyle. This research aimed to perceive the role of product communication in consumer trust throughout Burgreens’ case study. This research applies quantitative methods and purposive sampling techniques. The populations of this research are involving the consumers of Burgreens’ within the Google form online distribution and the data are analyzed by SPSS. In this research, product communication influences consumer trust